Analisis Komperatif Implementasi Kurikulum Pendidikan Agama Islam di Sekolah Islam dan Sekolah Umum - Umi Khalimatul Dzikriah; Alfi Rohmatul Azizah; Listyawati Nur Rohmah; Sulis Sulastri; Purnomo (IIQ An Nur Yogyakarta, 2026)
This study aims to analyze the differences in the implementation of the Islamic Religious Education (PAI) curriculum between Islamic schools or madrasahs and general schools, with a primary focus on the learning ecosystem and the quality of assessment in shaping students’ religious competencies. Researchers employ a literature review approach by referring to the analytical model proposed by Creswell. Data were collected through a review of various academic sources, particularly from Google Scholar, using relevant keywords such as PAI curriculum, learning processes, school religious culture, and authentic assessment. The selected articles were then screened based on their relevance, credibility, and recency, and analyzed using thematic analysis techniques. The findings reveal three main points. First, the differences in PAI curriculum implementation do not lie in the curriculum documents, but rather in the learning ecosystem, where madrasahs tend to have a stronger religious culture through habituation, while general schools are more formal and limited to instructional hours. Second, assessment practices in madrasahs are more comprehensive, covering cognitive, affective, and psychomotor domains, whereas general schools still predominantly rely on written tests. Third, both types of institutions are essentially complementary; therefore, general schools need to strengthen authentic assessment and religious habituation, while madrasahs need to develop more adaptive and critical pedagogical approaches. This study highlights the importance of enhancing teachers’ capacity, improving affective and psychomotor assessment instruments, and creating a balanced PAI learning ecosystem that integrates religious values with critical thinking skills.